The ethical challenge of genetic testing for breast cancer - Surbone, Antonella (Medicina e Morale, 1999)
The scientific importance of our recently acquired ability to test for heredity predisposition to breast and ovarian cancers is paralleled only by its social and ethical relevance. Dilemmas are common in all genetic testing, but they assume particular nuances in the setting of breast cancer. Due to its devastating nature and to its increasing incidence, breast cancer is a central issue in women's health. Breast cancer patients and women in general are often deeply involved in understanding the disease process and the treatment options, as they are in discussing the psychological, social and moral ramifications. This paper is a reflection upon some qualitative aspects of the debate that surrounds genetic testing for breast and ovarian cancer, as they have emerged in my encounters with breast cancer patients prior to their decision to consider genetic testing. The five recurrent themes identified in those conversations may or may not be representative of other practice situations, but they illustrate some fundamental philosophical, ethical and moral questions which exist at the core of our human essence and of our moral agency, and which point to the unavoidable intertwinement of medicine, culture, normativity and philosophy, vis-à-vis the many questions raised by genetics. The Author has intentionally refrained from questionnaires, which could betray the complexity of our thinking process, and from the vignettes, as they could betray confidentiality. The paper concludes that the correct answers to the dilemmas posed by genetic testing for breast cancer predisposition can only arise from a blend of medical, social and philosophical analysis.